2023
DOI: 10.1111/1744-7917.13285
|View full text |Cite
|
Sign up to set email alerts
|

Complex interactions among insect viruses‐insect vector‐arboviruses

Hui Wang,
Qian Chen,
Taiyun Wei

Abstract: Insects are the host or vector of diverse viruses including those that infect vertebrates, plants, and fungi. Insect viruses reside inside their insect hosts and are vertically transmitted from parent to offspring. The insect virus–host relationship is intricate, as these viruses can impact various aspects of insect biology, such as development, reproduction, sex ratios, and immunity. Arthropod‐borne viruses (arboviruses) that cause substantial global health or agricultural problems can also be vertically tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…From another perspective, our results align with previous studies on vector insects being responsible for transmitting plant pathogens and confirmed that the midgut and salivary glands of insects serve as a significant impediment for pathogen transmission ( Hogenhout et al., 2008 ; Wang et al., 2023 ). A significant indication of the transmission capability of an insect vector related to plant pathogens, is the ability of the pathogen to infiltrate particular cells within the salivary glands of vector insects, and amass in substantial quantities, thereby attaining a sufficient concentration to facilitate transmission of the plant pathogen ( Weintraub and Beanland, 2005 ; Galdeano et al., 2020 ; Wang et al., 2023 ).…”
Section: Discussionsupporting
confidence: 90%
“…From another perspective, our results align with previous studies on vector insects being responsible for transmitting plant pathogens and confirmed that the midgut and salivary glands of insects serve as a significant impediment for pathogen transmission ( Hogenhout et al., 2008 ; Wang et al., 2023 ). A significant indication of the transmission capability of an insect vector related to plant pathogens, is the ability of the pathogen to infiltrate particular cells within the salivary glands of vector insects, and amass in substantial quantities, thereby attaining a sufficient concentration to facilitate transmission of the plant pathogen ( Weintraub and Beanland, 2005 ; Galdeano et al., 2020 ; Wang et al., 2023 ).…”
Section: Discussionsupporting
confidence: 90%
“…Both vertical and horizontal transmission of ISVs are thought to exist in host insect populations [ 1 , 2 ]. Symbiotic ISVs display intricate interactions with their host insects, despite not causing evident pathogenic symptoms [ 1 , 4 ]. For instance, symbiotic partiti-like viruses identified in African armyworms have been shown to reduce the growth rate and reproductive capability of the host insect while concurrently increasing their resistance to a nucleopolyhedrovirus (NPV) [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a considerable number of viruses lacking obvious pathogenicity have been identified in insects, many of which are known as insect-specific viruses (ISVs) [ 2 ]. ISVs are abundant, and diverse and engage in complex interactions with host insects, enhancing our understanding of the insect virome and insect–virus coevolution [ 4 , 5 , 6 ]. Numerous insect-borne pathogenic viruses together with ISVs can infect and proliferate within insects, indicating a close phylogenetic relationship between them.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of next-generation sequencing technology, a large number of symbiotic viruses have been discovered in N. lugens, such as Nilaparvata lugens reovirus [3], Himetobi P virus (HiPV) [4], Nilaparvata lugens commensal X virus (NLCXV) [4], Nilaparvata lugens honeydew virus (NLHV) [5,6], and Nilaparvata lugens C virus (NlCV) [7]. The presence of symbiotic viruses can affect the behaviour and performance of their insect hosts, potentially influencing the host's ability to act as vectors for arboviruses [8,9]. A previous study also indicated that NLRV can interfere with the transmission and proliferation of RRSV in BPH [10].…”
mentioning
confidence: 99%